Volume 2A: Turbomachinery — Axial Flow Fan and Compressor Aerodynamics 2021
DOI: 10.1115/gt2021-58708
|View full text |Cite
|
Sign up to set email alerts
|

Performance of a Subsonic Compressor Airfoil With Upstream, End-Wall Injection Flow

Abstract: The performance of a compressor stator airfoil with end-wall injection was studied experimentally and computationally. The geometry was a high-speed, subsonic, linear cascade. The independent variables studied were airfoil incidence angle and mass flow rate of end-wall injection upstream of the stator. The end-wall injection was intended to simulate upstream “leakage” through hardware gaps in the end-walls of gas-turbine engines. The exit of the cascade was interrogated experimentally by a five-hole-probe and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
(12 reference statements)
0
1
0
Order By: Relevance
“…In recent years, the high-load axial compressor has been widely developed (Xiangjun et al 2014;Pope et al 2021;Ma et al 2019), and serious threedimensional (3D) corner separation has been found near the end-wall of the last-stage stator. This corner separation is formed mainly as a result of the development of the end-wall boundary layer, which leads to flow loss and a deteriorated flow field (Denton 1993).…”
Section: Introductionmentioning
confidence: 99%
“…In recent years, the high-load axial compressor has been widely developed (Xiangjun et al 2014;Pope et al 2021;Ma et al 2019), and serious threedimensional (3D) corner separation has been found near the end-wall of the last-stage stator. This corner separation is formed mainly as a result of the development of the end-wall boundary layer, which leads to flow loss and a deteriorated flow field (Denton 1993).…”
Section: Introductionmentioning
confidence: 99%